Examining social identity and intrateam moral behaviours in competitive youth ice hockey using stimulated recall. Issue 20 (18th October 2017) - Bruner, Mark W.; Boardley, Ian D.; Allan, Veronica; Root, Zach; Buckham, Sara; Forrest, Chris; Côté, Jean
ABSTRACT: Social identity – identity formed through membership in groups – may play an important role in regulating intrateam moral behaviour in youth sport (Bruner, M. W., Boardley, I., & Côté, J. (2014). Social identity and prosocial and antisocial behavior in youth sport. Psychology of Sport and Exercise, 15 (1), 56–64. doi:10.1016/j.psychsport.2013.09.003). The aim of this study was to qualitatively examine this potential role through stimulated recall interviews with competitive youth-ice-hockey players. Twenty-three players ( M age = 13.27 years, SD = 1.79) who reported engaging in high, median or low frequency of antisocial teammate behaviour (determined through pre-screening with the Prosocial and Antisocial Behaviour in Sport Scale [Kavussanu, M., & Boardley, I. D. (2009). The prosocial and antisocial behavior in sport scale. Journal of Sport and Exercise Psychology, 31 (1), 97–117. doi:10.1123/jsep.31.1.97]) were recruited from eight youth-ice-hockey teams in Canada. Interviews involved participants recalling their thoughts during prosocial/antisocial interactions with teammates, prompted by previously recorded video sequences of such incidents. Thematic analysis of interview data revealed all athletes – regardless of reported frequency of intrateam antisocial behaviour – felt prosocial interactions with teammates enhanced social identity. In contrast, the perceived influence of antisocial teammate behaviour on social identity differed depending on athletes' reported frequency of intrateam antisocial behaviour; those reporting low and median frequencies described how such behaviour undermines social identity, whereas athletes reporting high frequency did not perceive this effect. The study findings highlight the potential importance of intrateam moral behaviour and social identity for youth-sport team functioning.